Perancangan Dan Implementasi Media Pembelajaran Di SMK Al-Azhar Batam Menggunakan MDLC - Pratama, Jimmy; Chrissy, Joyce (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Education is very important for every generation, especially the younger generation. However, the biggest obstacle in learning Indonesian is the lack of creativity in learning methods and media, which makes students bored with following the teaching and learning process in class and feel they have understood the material given. SMK AL-AZHAR Batam is a private educational institution managed by the Al-Azhar Batam Islamic Education Foundation. The learning process of teaching materials which is still done manually by the teachers of SMK Al-Azhar Batam is by explaining and explaining contents of the book in a monotonous manner. In this report, the author will carry out practical work at the SMK Al-Azhar Batam School in making Indonesian language learning media at the SMK level. The media will be package in a video learning media. Learning Media will be developt using the MDLC (Multimedia Development Life Cycle) method. The Learning Media will be implemented in the teaching and learning process in schools at Al-Azhar Vocational School